Corrigendum Candidate Gene Locus for PHACE Syndrome. Am J Med Genet A. 2012;158(6):1363–1367. Doi:10.1002/ajmg.a.35341 (American Journal of Medical Genetics Part A, 2022)
Nonimmune hydrops fetalis (NIHF) is characterized by abnormal fluid accumulation in ≥ 2 fetal compartments and may be genetic. The incremental diagnostic yield of prenatal exome sequencing (ES) for NIHF following a negative standard workup was previously explored on 22 cases. We report ES findings in the remaining cohort and investigate the incremental yield of genome sequencing (GS) in cases without a definitive diagnosis from exome. Enrollment criteria and exome methodology for the Hydrops-Yielding Diagnostic Results of Prenatal Sequencing (HYDROPS) study were previously reported. Exomes without a definitive diagnosis were reviewed with updated clinical information and had GS if DNA was available. A genetic counselor returned the clinical reports. Overall, 50 exomes yielded 22 (44%) diagnoses and six possible diagnoses (12%). Nine new cases (9/28, 68%) had a diagnosis involving one of the following genes: RIT1, SOS1, RYR1, FLT4, LMOD2, KMT2D, PUF60, and BLTP1. Two additional cases were diagnosed upon reclassification of uncertain variants. GS of eligible ES cases resulted in an incremental diagnostic yield of 7% (1/14). ES and GS in NIHF significantly reduce the number of unexplained cases and guide clinical management and recurrence risks. Currently, the incremental diagnostic yield of GS over ES in NIHF remains under investigation. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT03911531.